Economics of Poultry Egg Marketing in Benin City, Edo State, Nigeria - Ekunwe, P.A.; Alufohai, G.O. (International Journal of Poultry Science, 2009)
This study examined the profitability of egg marketing as well as the market structure and marketing margin of poultry egg in Benin City, Edo state, Nigeria. Six markets (Uselu, Oliha, Ogida, Oba, Osa and New Benin markets) in Benin City were purposively selected for the study, after which ten egg sellers were randomly selected from each of the six markets giving a sample size of 60. Primary data were obtained through the use of a well-structured questionnaire and personal interview. The data obtained were analyzed using descriptive statistics, Gini coefficient and Gross margin. The results of the analysis showed that majority (96.7%) of the respondents were females. The mean age of the respondents was 45 years while the household size was 6 persons. A Gini coefficient of 0.81296 obtained in the study indicates a high level of inequality in income distribution among the respondents. The profitability analysis showed a gross margin per seller of 12,029.50 Naira ($104.61) and a net return per seller of 10,779.50 Naira ($93.74). Finally, a marketing margin of 60.67 Naira ($0.53) was obtained in the study area